Is a Depth Camera in Agreement with an Electromagnetic Tracking Device when Measuring Head Position?. Issue 1 (15th November 2021) - Burchell, Vienna-Jaye; Arblaster, Gemma; Buckley, David; Wheat, Jonathan
Introduction: Clinicians typically observe and describe abnormal head postures (AHPs) and may also measure them. Depth cameras have been suggested as a reliable measurement device for measuring head position using face-tracking technology. This study compared a depth camera (Microsoft Kinect) to a gold standard electromagnetic tracking system (Polhemus device) to measure head position. Method: Twenty healthy volunteers (mean age 21 years) had their head position simultaneously recorded using the depth camera (Kinect) and the electromagnetic tracking system (Polhemus). Participants were asked to make 30-degree head movements into chin up, chin down, head turn and head tilt positions. The head movement made and the stability of the head at each position were recorded and analysed. Results: Compared to the electromagnetic tracking system (Polhemus), the depth camera (Kinect) always measured a smaller head movement. Measurements with the two devices were not statistically significantly different for turn right (P = 0.3955, p > 0.05), turn left (P = 0.4749, p > 0.05), tilt right (P = 0.7086, p > 0.05) and tilt left (P = 0.4091, p > 0.05) head movements. However, the smaller depth camera measurement of chin up and chin down head movements were statistically significant, chin up (P = 0.0001, p < 0.01) and chin down (P = 0.0005, p < 0.001). At each eccentric position, the depth camera (Kinect) recordings were more variable than the electromagnetic tracking system (Polhemus). Conclusions: Compared to the electromagnetic tracking system (Polhemus), the depth camera (Kinect) was comparable for measuring head turns and tilts but was less accurate at measuring chin up and chin down head positions. Further research is needed before the depth cameras are considered for clinical recordings of head position.